Peran Biro Kesejahteraan Rakyat Provinsi Jawa Timur dalam Upaya Penurunan Stunting di Provinsi Jawa Timur Melalui Penguatan Tim Pembina Unit Kesehatan Sekolah (TP UKS/M) - Hardiansyah, Ferdian Putra Dwi; Arundinasari, Indira (VISA: Journal of Vision and Ideas, 2024)
Indonesia is facing serious issues regarding nutrition, particularly evident in the high number of cases of malnutrition among toddlers and similar problems experienced by school-age children, both boys and girls, a condition referred to as stunting. Micro data analysis (Riskesdas 2013) reveals that East Java Province is ranked 15th among all provinces in Indonesia with a prevalence rate of 35.7% for stunting. Referring to Presidential Regulation Number 72 of 2021, the East Java Provincial Government is striving to expedite the reduction of stunting, especially within the scope of schools or madrasahs. The East Java Provincial Government has issued Governor's Decree No. 188/330/KPTS/013/2022 concerning the School or Madrasah Health Enterprise Development Team in East Java Province. Therefore, the People's Welfare Bureau of East Java Province, as a facilitator in the basic healthcare sector, plays a role in accelerating the reduction of stunting through the School or Madrasah Health Enterprise Development Team in East Java. This study adopts a qualitative approach using the descriptive analysis method by Miles and Huberman's model. The research utilizes primary data obtained through interviews, observations, group discussions, as well as secondary data collected through literature review. The findings indicate that the People's Welfare Bureau of East Java Province is pivotal in addressing the reduction of stunting through the School or Madrasah Health Enterprise Development Team, which has become the focus of the East Java Provincial Government's actions. Collaborating with relevant stakeholders in tackling the acceleration of stunting reduction through the School or Madrasah Health Enterprise Development Team can aid in achieving the target percentage of stunting situations in East Java, reducing to 13.5% by 2024. Through the School or Madrasah Health Enterprise Development Team, it is hoped that the People's Welfare Bureau can actively contribute to the success of the government's program regarding the national movement to prevent and reduce stunting.